POSSIBILITY OF USING BIOCHEMICAL AND HEMATOLOGICAL PARAMETERS IN EVALUATING ADNEXAL MASSES - Petrić, Aleksandra Nadežda (Acta medicae Medianae, 2022)
Current diagnostic approach to adnexal masses (medical history, clinical examination, transvaginal sonography, tumour markers) does not provide an accurate prediction for potential malignancy. There is a possibility of using hematological and biochemical parameters (platelets count, neutrophil/lymphocyte ratio, platelet/lymphocyte ratio, platelet distribution width, level of C-reactive protein) in predicting ovarian malignancy. A retrospective study was conducted. Analysis of aforementioned parameters was performed in patients with histopathologically verified benign/malignant ovarian tumours. CRP levels, total count of granulocytes, and total count of platelets were statistically significantly higher in patients with malignant changes (p < 0.001, p = 0,001, or p = 0.023). Total lymphocytes count was statistically significantly lower in patients with malignant changes (p < 0.001). Platelet count was statistically significantly higher in patients with stage III (p = 0.011). Pl/LY ratio was statistically significantly higher in patients with stage III (p = 0.043). CRP was statistically significantly higher in stage III (p < 0.001). Lymphocyte count was statistically significantly lower in stage III (p < 0.001), and granulocyte count was statistically significantly higher in stage III (p = 0.001). Platelet count was statistically significantly higher in stage III (p = 0.001). MPV was statistically significantly lower in stage III (p = 0.031). Pl/Ly ratio was statistically significantly higher in patients with stage III (p = 0.044). Analyzed biochemical and hematological parameters are of limited utility in differentiating benign from malignant ovarian masses. Elevated levels of C-reactive protein, neutrophils and platelets suggest potentially malignant ovarian masses. Analyzed biochemical parameter (high levels of C-reactive protein, reduced lymphocyte count, increased granulocyte count, increased platelet count, increased PLR, as well as lower MPV values) may suggest advanced malignancy.